Development of the Information Society in Czech Republic, Poland and Slovakia - Feltynowski, Marcin (Comparative Economic Research. Central and Eastern Europe, 2012)
The article is presenting facts about the politics carried on the EU concerning development of the information society in Czech Republic, Poland and Slovakia - countries that in 2004 became members of the EU. Enlargement of the EU structures allowed for more dynamic development of these countries in the information society context. The situation of each country was presented by indicators describing the household and the community situation in information society. Indicators was gained from Eurostat system. The universality of these indicators lets to the assessment of the level and dynamics of development in relation to the EU average. Comparison of Poland and its southern neighbors allows also to observe changes that occur and may allow better progress in this field.